PEMBUATAN PETA SITUASI SKALA 1:500 DUSUN KALICANGAK DAN DUSUN KALITURI DESA BELUK KECAMATAN BAYAT KABUPATEN KLATEN PROVINSI JAWA TENGAH - , JOHAN ARIYANTONI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final project as a way to increase understanding and skill of the measurement and mapping of the real in the field. Measurements were performed to obtain a high detailed and planimetric detail in these areas. The details will be processed to form a map of the situation. Mapping method used is the measurement of the horizontal control framework is the horizontal angle measurement, electronic distance and azimuth, then the measurement of vertical control framework, detailed measurements, and the last depiction of digital maps. The result is a four-sheet map of the situation scale 1: 500 2 exact location in the hamlet Kalituri and Kalicangak hamlets, Beluk villages, Bayat subdistrict, Klaten district, Central Java province.